Recurrent Dermatofibrosarcoma Protuberans with Fibrosarcomatous Transformation: A Case Report - Aji, Haivan Kusuma; Kiki Akhmad Rizki (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Dermatofibrosarcoma protuberans (DFSP) is a rare cutaneous sarcoma with a propensity for local recurrence but a low risk of distant metastasis. Fibrosarcomatous transformation (FS-DFSP) is a rare but aggressive variant associated with increased metastatic potential. Case presentation: We present the case of a 39-year-old male with recurrent DFSP involving the scalp, mandible, and humerus, complicated by fibrosarcomatous transformation and distant metastases to the lungs and bones. The patient underwent multiple excisions, radiation therapy, and systemic treatments including chemotherapy and imatinib, but ultimately experienced disease progression. Conclusion: This case highlights the challenges in managing recurrent DFSP with fibrosarcomatous transformation. The rarity of this entity necessitates a high index of suspicion for early diagnosis and aggressive multidisciplinary management to improve patient outcomes. Further research is needed to identify effective treatment strategies for this aggressive variant of DFSP.